Biochemical and structural analyses of the nucleosome containing human histone H2A.J. (3rd December 2019) - Tanaka, Hiroki; Sato, Shoko; Koyama, Masako; Kujirai, Tomoya; Kurumizaka, Hitoshi
Abstract: Histone H2A.J, a histone H2A variant conserved in mammals, may function in the expression of genes related to inflammation and cell proliferation. In the present study, we purified the human histone H2A.J variant and found that H2A.J is efficiently incorporated into the nucleosome in vitro . H2A.J formed the stable nucleosome, which accommodated the DNA ends. Mutations in the H2A.J-specific residues did not affect the nucleosome stability, although the mutation of the H2A.J Ala40 residue, which is conserved in some members of the canonical H2A class, reduced the nucleosome stability. Consistently, the crystal structure of the H2A.J nucleosome revealed that the H2A.J-specific residues, including the Ala40 residue, did not affect the nucleosome structure. These results provide basic information for understanding the function of the H2A.J nucleosome.